Effects of synbiotic supplementation on growth performance, carcass characteristics, meat quality and muscular antioxidant capacity and mineral contents in broilers. (25th February 2017) - Cheng, Yefei; Chen, Yueping; Li, Xiaohan; Yang, Weili; Wen, Chao; Kang, Yuru; Wang, Aiqin; Zhou, Yanmin
Abstract: BACKGROUND: The present study aimed to investigate the effects of dietary synbiotic supplementation on growth performance, carcass composition, meat quality and muscular antioxidant capacity, and mineral contents in broilers. Accordingly, 96 day‐old male broiler chicks (Arbor Acres Plus; Aviagen, Huntsville, AL, USA) were randomly allocated to two groups, and each group consisted of six replicates with eight chicks each. Birds were fed a corn‐soybean meal basal diet supplemented with either 0 or 1.5 g kg −1 synbiotic, consisting of probiotics ( Bacillus subtilis, Bacillus licheniformis and Clostridium butyricum ) and prebiotics (yeast cell wall and xylooligosaccharide) from 1 to 42 days of age. RESULTS: Compared with the control group, supplementation with a synbiotic increased average daily gain ( P < 0.05) but reduced feed/gain ratio ( P < 0.01) in broilers from 1 to 42 days of age. Similalrly, dietary synbiotic inclusion increased breast yield ( P < 0.05) but decreased abdominal fat ( P < 0.01) in broilers. The breast muscle pH value at 24 h postmortem in broilers was elevated with the incorporation of synbiotic ( P < 0.05). By contrast, synbiotic supplementation lowered the cooking loss during heat treatment in a water bath, malondialdehyde content, and total Cr content in the thigh muscle in broilers ( P < 0.05). CONCLUSION: Dietary synbiotic supplementation into the diet of broilers may be an effective method for improving growth performance and carcass compositions, resulting in the production of meat with a favorable quality and oxidative stability. © 2017 Society of Chemical Industry